COVID-19 lung injury as a primer for immune checkpoint inhibitors (ICIs)-related pneumonia in a patient affected by squamous head and neck carcinoma treated with PD-L1 blockade: a case report. Issue 2 (11th February 2021) - Dipasquale, Angelo; Persico, Pasquale; Lorenzi, Elena; Rahal, Daoud; Santoro, Armando; Simonelli, Matteo
Abstract : By the beginning of the global pandemic, SARS-CoV-2 infection has dramatically impacted on oncology daily practice. In the current oncological landscape, where immunotherapy has revolutionized the treatment of several malignancies, distinguishing between COVID-19 and immune-mediated pneumonitis can be hard because of shared clinical, radiological and pathological features. Indeed, their common mechanism of aberrant inflammation could lead to a mutual and amplifying interaction. We describe the case of a 65–year-old patient affected by metastatic squamous head and neck cancer and candidate to an experimental therapy including an anti-PD-L1 agent. COVID-19 ground-glass opacities under resolution were an incidental finding during screening procedures and worsened after starting immunotherapy. The diagnostic work-up was consistent with ICIs-related pneumonia and it is conceivable that lung injury by SARS-CoV-2 has acted as an inflammatory primer for the development of the immune-related adverse event. Patients recovered from COVID-19 starting ICIs could be at greater risk of recall immune-mediated pneumonitis. Nasopharyngeal swab and chest CT scan are recommended before starting immunotherapy. The awareness of the phenomenon could allow an easier interpretation of radiological changes under treatment and a faster diagnostic work-up to resume ICIs. In the presence of clinical benefit, for asymptomatic ICIs-related pneumonia a watchful-waiting approach and immunotherapy prosecution are suggested.